A rare face of "PHACE" syndrome with Dandy-Walker malformation, microphthalmia with leukocoria, hearing loss and involuting segmental facial hemangioma - Anup Kumar Tiwary; Dharmendra Kumar Mishra; Gunjan Jha (Wolters Kluwer Medknow Publications, 2017)
The acronym "PHACE" refers to the syndromic association of posterior fossa anomalies, hemangioma, arterial lesions, cardiac abnormalities/coarctation of the aorta, and eye anomalies. Till now, less than 400 cases of PHACE syndrome have been reported in the medical literature. Its etiopathogenesis is still unknown, and a great deal of genetic and molecular research is required. Moreover, there is always a high probability of misdiagnosis due to the certain factors such as mildly symptomatic patients, hasty diagnosis of relatively common simulating syndromic entities, and low awareness among medical fraternity about the standard diagnostic criteria for PHACE syndrome. Therefore, we report here a case of PHACE syndrome in a 2-year-old female child presenting with Dandy-Walker malformation, microphthalmia, leukocoria, hearing loss, and regressing lesions of large facial infantile hemangioma.